Building Resilient Start-up Ecosystems in the Digital Era: A Narrative Review - Slamet, Asep Gunawan; Achaddiah, Bella Noer; Yuni T, Veronika (Novatio : Journal of Management Technology and Innovation, 2024)
This narrative review explores the critical factors influencing the growth and resilience of technology-driven start-ups in the digital era. Literature was systematically collected from Scopus, Web of Science, and Google Scholar, covering peer-reviewed studies from 2010 to 2025. Thematic analysis and bibliometric mapping were employed to synthesize findings across diverse contexts. Results show that funding access, supportive regulation, and strong networks remain fundamental pillars for entrepreneurial success. Entrepreneurship education that integrates digital competencies and experiential learning strengthens entrepreneurial capacity, while digital technologies such as artificial intelligence, the Internet of Things, and blockchain underpin disruptive business models that enhance competitiveness. However, persistent barriers exist, including gender inequality in access to resources and technostress among founders, underscoring the need for inclusivity and well-being support. Comparative analysis reveals that advanced economies benefit from robust infrastructure and funding mechanisms, while developing regions, despite resource constraints, demonstrate adaptive localized innovations. The review highlights the importance of coordinated policy, education, and practice in creating equitable and resilient ecosystems. Strengthening financial access, regulatory clarity, digital infrastructure, gender inclusivity, and well-being initiatives emerges as a strategic priority for fostering sustainable technology-driven entrepreneurship.